Solving of nonstandard exercises on oscillatory motion - Mukhamedov M. R. (Summer Vacation, 2016)
the article explores the examples of nonstandard exercise solving on oscillatory motion.
Keywords: колебательное движение; колебательные системы; законы колебательного движения; решение задач по физике; oscillatory motion; oscillatory systems; oscillatory motion laws; solving of physics exercises